Studying visual communication - Worth, Sol (University of Pennsylvania Press, 1981)
"Worth had courage and originality enough not to take pictures for granted, but thought and struggled with some of the most difficult problems that cinematographers (and researchers in visual media) are faced with."—Edward T. Hall